Petrogenesis of Mesoproterozoic Granites of the Swartoup Hills Region, Kakamas Domain, Namaqua Belt, South Africa - Büttner, Steffen Hermann; Prevec, Stephen Anthony; Schmeldt, Graeme Alvin (Frontiers in Earth Science, 2021)
The Swartoup and Polisiehoek plutons in the Swartoup Hills (South Africa) formed during an episode of significant magma emplacement in the Mesoproterozoic Namaqua Sector of the Namaqua Metamorphic Province. They intruded into mid-crustal metasedimentary rocks of the metapelitic Koenap and mafic to carbonatic Bysteek Formations during and shortly after the ~1200-1220 Ma regional metamorphic peak that reached ultra-high temperatures. Subsequent to pluton emplacement, the crust underwent regional high-temperature deformation during slow near-isobaric cooling. A further episode of pluton emplacement associated with fluid circulation truncated the first order regional tectonic structures at ~1100 Ma. Based on their petrography, the Swartoup pluton has been subdivided into leuco-granitoids with biotite as the sole mafic phase, pyroxene granitoids and garnet bearing granitoids, which may contain significant biotite. These subgroups display distinctive geochemical variations from one another, and from the Koenap Formation migmatites and the Polisiehoek granites, which are exposed nearby. Incompatible trace element distributions suggest that the Swartoup and Polisiehoek granitoids represent predominantly A-type granite magma, probably derived from a slightly older granulitic lower crust. The magmas incorporated significant amounts of juvenile mantle magma (εNd1200 of ca. -5, and LREE-depleted), but require small amounts of older, early to late Paleoproterozoic crust. Particularly close to contacts to the calcic Bysteek Formation, localised contamination of the Swartoup granites by supracrustal carbonates is evident. A relatively pervasive alkali metasomatic effect is manifested strongly in the initial 87Sr/86Sr and LILE profiles of the Polisiehoek granites in particular, as well as in some of the Swartoup pyroxene granitoids, which could be either a symptom of CO2 metasomatism related to the Bysteek Formation carbonates, or to post-magmatic fluid metasomatism, perhaps linked to regional shearing. The comparison of our results with literature data suggests that similar sources, A-type granitic, Meso- to Paleoproterozoic crustal, and enriched mantle, have contributed, in locally differing proportions, to granites in most parts of the Namaqua Sector. Most likely these plutons were generated during crustal and mantle melting in in a long-lived hot continental back-arc environment.